2009
DOI: 10.1159/000223415
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Evaluation of Patients with a Homozygous R450H Mutation of the TSH Receptor Gene

Abstract: Background/Aim: The R450H mutation of the TSH receptor (TSHR) gene has been frequently observed in Japanese patients with resistance to TSH. The purpose of this study was to clarify the phenotype of patients with a homozygous R450H mutation of the TSHR gene; the mutant receptor has previously demonstrated moderately impaired function in vitro. Methods: We performed a clinical investigation of 5 Japanese patients who had hyperthyrotropinemia as neonates, in whom a homozygous R450H mutation of the TSHR gene had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 53 publications
(44 reference statements)
2
20
0
2
Order By: Relevance
“…Homozygotes had a more severe phenotype manifested by higher TSH levels at diagnosis and at last visit (mean TSH 53.6 vs. 9.24, p < 0.0001; 62.07 vs. 9.79, p = 0.0005, respectively). Despite the significantly higher serum TSH concentrations, mean serum fT4 levels did not differ between homozygotes and heterozygotes (13.96 vs. 16.27 at diagnosis, p = 0.175; 12.53 vs. 14.35 at last visit, p = 0.1006, respectively). Compound heterozygous subjects had one severe mutation and one very mild one (L653V/ P68S) presenting with a moderate phenotype, reflecting the weak functional effect of the P68S mutation (9,11).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Homozygotes had a more severe phenotype manifested by higher TSH levels at diagnosis and at last visit (mean TSH 53.6 vs. 9.24, p < 0.0001; 62.07 vs. 9.79, p = 0.0005, respectively). Despite the significantly higher serum TSH concentrations, mean serum fT4 levels did not differ between homozygotes and heterozygotes (13.96 vs. 16.27 at diagnosis, p = 0.175; 12.53 vs. 14.35 at last visit, p = 0.1006, respectively). Compound heterozygous subjects had one severe mutation and one very mild one (L653V/ P68S) presenting with a moderate phenotype, reflecting the weak functional effect of the P68S mutation (9,11).…”
Section: Resultsmentioning
confidence: 84%
“…There is only one longitudinal study of subjects with TSHR mutations, which describes five subjects homozygous for the R450H TSHR mutation who presented with congenital hyperthyrotropinemia. Of the five individuals, one developed frank hypothyroidism during adolescence (16), supporting the need for long-term follow-up, especially in homozygotes.…”
Section: Discussionmentioning
confidence: 81%
“…This controversy is also reflected by the variable use of L-T 4 therapy in this multicenter study. In partial TSH resistance, previous studies suggested that the presence of higher TSH concentrations may be sufficient to compensate for the diminished thyroid sensitivity and thus stimulate an adequate production of thyroid hormones (9,14). Here, despite that several patients did not receive replacement therapy, they had no obvious neurological or growth abnormalities.…”
Section: Discussionmentioning
confidence: 63%
“…In contrast to subclinical hypothyroidism in the context of AITD, the thyroidal compensation in mild to moderate RTSH is expected to be clinically stable with no progression toward true hypothyroidism or spontaneous regression toward normal TSH levels. In contrast, development of overt hypothyroidism at the age of 15 years was shown in a patient homozygous for the R540H mutation presenting with compensated hypothyroidism in infancy, but not in an additional four subjects with the same genotype after long-term follow-up [21].…”
Section: Ta (Tm-5) -Annealing Temperature F -Forward Sequence (5´→ 3mentioning
confidence: 75%